Organizational diversity in the fusion process of a financial institution (Dimensión Empresarial, 2017)
In this research, we addressed the meeting of cultures, with the aim of exploring the relationship of symbolic in a financial institution, then the process of acquiring another institution. The theoretical approach is used to analyze the perspective of Elias and Scotson (1994) on the processes of stigmatization of foreign social groups as a crucial factor in understanding the relationship of symbolic, the concept of Robert Park on marginal man and the concept of Turner on liminality. As a result, we show that members of the acquired company are seen as those who threaten the established culture.ResumenEn esta investigación, abordamos el encuentro de culturas, con el objetivo de explorar las relaciones de dominación simbólica en una institución financiera, posteriormente al proceso de adquisición de otra institución. El abordaje teórico utilizado para el análisis es la perspectiva de Elias y Scotson (1994) sobre los procesos de estigmatización de los grupos sociales extranjeros como factor crucial en el entendimiento de la relación de dominación simbólica, el concepto de Robert Park sobre el hombre marginal y de Turner sobre liminaridad. Como resultados, evidenciamos que los miembros de la empresa adquirida son vistos como aquellos que amenazan la cultura establecida.ResumoNesta pesquisa, abordamos o encontro das culturas, com o objetivo de explorar as relações de dominação simbólica em uma instituição financeira, após o processo de aquisição de outra instituição. A abordagem teórica utilizada para a análise é a perspectiva de Elias e Scotson (1994) sobre os processos de estigmatização de grupos sociais estrangeiros como fator crucial na compreensão da relação de dominação simbólica, o conceito de Robert Park no homem marginal e Turner na liminaridade. Como resultados, mostramos que os membros da empresa adquirida são vistos como aqueles que ameaçam a cultura estabelecida.
Keywords: culture; diversity; established and outsiders